თვითერთის, საზღვარი-ერთისა და ჰენადების გაგება პროკლეს მეტაფიზიკაში - ქირია ანა (ლოგოსი, 2022)
The present paper aims to understand functions and interrelationships of different types of the superessential One, which are the One Itself, the Limit-One, and Henads, in Proclus’ metaphysics. The paper is divided into six sections. In the first section, after thematizing general characteristics of a philosophical system and analyzing proposition 11 of Elementatio theologica, we emphasize Proclus’ systematic nature and point out some leitmotifs of his metaphysical (theological) system. In the second section, we elucidate the scientific character of the Proclean metaphysical (theological) theory, which shows in its precision and accuracy, differential certainty, methodological clarity, consistency, and rationality. The third section concerns Proclus’ conception of a cause and causal process, eventually resulting in the identification of the first real cause of everything with the first Limit, which is simultaneously the first real One for Proclus. In the fourth section, we deal with the Proclean understanding of the unspeakable cause (ἄρρητος αἰτία), which while being the One itself (αὐτοέν), is paradoxically better than the One. In the fifth section, we examine Henads and attempt to solve main issues related to this enigmatic part of Proclean metaphysics. In the last section, we sum up a relationship between the One itself, the Limit-One along with its counterpart, i.e. the Unlimited, and Henads.